PEMBERDAYAAN EKONOMI MASYARAKAT PEDESAAN MELALUI KELOMPOK USAHA - Arif Sofianto (Politeknik Kesejahteraan Sosial, 2017)
The purpose of this study was to; 1). determine the role of the group in catfish cultivation in Wonosari Village and Podorejo Village, 2). analyzing the institutional constraints catfish cultivation in Wonosari Village and Podorejo Village, 3). designing ideal institutional model of catfish cultivation in Wonosari Village and Podorejo Village. This study used a qualitative descriptive method. Informants involved in the research include members of the the Mino Sari and Maju Makmur. This study use the interactive model as developed by Miles and Huberman. The conclusion of this study were: 1). The role of the research sites is to provide guidance, social cohesiveness, information science and technology and capital. 2). Constraints experienced by the group is the internal conflict, lack of trust, lack of capital capacity, and dependence on the leadership figure. 3). The ideal is to have a group of strong social capital, a clear division of tasks, members of the coaching ability, capital assistance, seed fulfillment, the fulfillment of alternative feed and assist the sales and processing of crops.